Pyrolysis-gas chromatography : mass spectrometry analysis of di- and triterpenoids - Renzi, Francesca (2017)
The objective of this work was to study a specific class of extractives existing in lignocellulosic biomass and more precisely in wood materials, and their thermochemical behavior during pyrolysis. The focus was centered on the class of terpenes and terpenoids; specifically two model compounds, abietic acid and betulinol, were chosen to represent the subclasses of di- and triterpenoids, respectively. The model compounds were investigated via pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) and the main objective was to study their product profiles and characteristic fragmentations, as well as the influence of specific variables (pyrolysis temperature and time) on pyrolysis products. Pyrolysis experiments were performed at three different temperatures (700, 600, and 500°C) with two different pyrolysis times (20 and 5 seconds). The MS spectra indicated that the fragments obtained from abietic acid and betulinol, under the chosen conditions, were mainly aromatics in nature, especially at the higher temperature, whereas at the lower temperature different fragmentation products of the original molecule were also present. Among the pyrolytic products, benzene, indene, naphthalene, and their derivatives, mainly methylated, were dominant and common to both model compounds. Phenanthrene derivatives were only found during pyrolysis of abietic acid, due to the stability of the phenanthrene carbon skeleton, which is a characteristic of tricyclic resin acids. A general trend could be seen at the higher pyrolysis temperature and longer time enhancing the formation of the detected compounds. Overall, pyrolysis temperature was shown to be a more influential parameter than pyrolysis time. The relevance of this type of research relies on the fact that investigations on model compounds can improve the understanding of the whole biomass behavior under different pyrolytic conditions. In addition to that, studies on the thermochemical behavior of lignocellulosic materials have a key role in evaluating the feasibility of producing certain fuels and chemicals from this renewable and abundant resource. This can offer an attractive opportunity for industry in the manufacture of various wood-based chemicals, fuels, and similar products, as an alternative to those derived from fossil resources.